James Baldwin: Interventions: A Session at the 2019 Modern Language Association Convention - Robert Jackson; Sharon P. Holland; Shawn Salvant (James Baldwin Review, 2019)
“Interventions” was the organizing term for the presentations of three Baldwin scholars at the Modern Language Association Convention in Chicago in January of 2019. Baldwin’s travels and activities in spaces not traditionally associated with him, including the U.S. South and West, represent interventions of a quite literal type, while his aesthetic and critical encounters with these and other cultures, including twenty-first-century contexts of racial, and racist, affect—as in the case of Raoul Peck’s 2016 film I Am Not Your Negro—provide opportunities to reconsider his work as it contributes to new thinking about race, space, property, citizenship, and aesthetics.